Thoracoscopic pneumonectomy for an esophageal lung in a newborn: A case report - Valentina Saavedra Taboada; Eduardo Leopold González; Angela Cristino; Waldo Osorio Catalan; Claudio Arce Fricke; Patricio Varela Balbontín (Elsevier, 2023)
Introduction: The esophageal lung is an extremely infrequent congenital malformation within the broncho-pulmonary foregut malformations (CBPFM) spectrum, characterized by the presence of a communication between the esophagus and the lung tissue. Case presentation: A 9-day-old male newborn was transferred from a secondary center to our center on suspicion of a tracheo-esophageal fistula after a chest x-ray revealed opacification of the entire right lung, along with tracheal deviation and mediastinal shift, indicating severe right lung atelectasis. A non-contrast chest tomography showed right lung atelectasis and a bronchus-esophagus communication. The patient was asymptomatic on arrival. A bronchoscopy was done on day of life 10, and revealed absence of a carina and a single left-sided main bronchus. Additionally the patient underwent an esophagoscopy that revealed an opening on the right side of the distal third of the esophagus. Contrast studies confirmed the broncho-esophageal communication and the absence of a right main stem bronchus arising from the trachea. At 17 days of age the patient underwent a thoracoscopy. The esophageal bronchus was identified and a pneumonectomy was completed. The patient was extubated 1 day after the operation. At 6 months of follow up he is thriving well and has no oxygen requirements. Conclusion: This case emphasizes the importance of early diagnosis in cases of esophageal lung, which can be accomplished by a combination of radiological and endoscopic studies. Pneumonectomy is the treatment of choice.